A new estimation technique of sovereign default risk - Mehmet Ali Soytas; Engin Volkan (Central Bank Review (CBR), 2016)
Using the fixed-point theorem, sovereign default models are solved by numerical value function iteration and calibration methods, which due to their computational constraints, greatly limits the models' quantitative performance and foregoes its country-specific quantitative projection ability. By applying the Hotz-Miller estimation technique (Hotz and Miller, 1993)- often used in applied microeconometrics literature- to dynamic general equilibrium models of sovereign default, one can estimate the ex-ante default probability of economies, given the structural parameter values obtained from country-specific business-cycle statistics and relevant literature. Thus, with this technique we offer an alternative solution method to dynamic general equilibrium models of sovereign default to improve upon their quantitative inference ability.
Keywords: 330; Sovereign default risk; Hotz-Miller estimation; Endogenous default risk; Conditional choice probabilities; PML; GMM